An air-stable, neutral phenothiazinyl radical with substantial radical stabilization energy - Sigmund, Lukas M.; Ebner, Fabian; Jöst, Christoph; Spengler, Jonas; Gönnheimer, Nils; Hartmann, Deborah; Greb, Lutz (Chemistry - a European journal, 2020)
The vital effect of radical states on the pharmacological activity of phenothiazine-based drugs has long been speculated. Whereas cationic radicals of N-substituted phenothiazines show high stability, the respective neutral radicals of N-unsubstituted phenothiazines have never been isolated. Herein, the 1,9-diamino-3,7-di-tert-butyl-N1,N9-bis(2,6-diisopropylphenyl)-10H-phenothiazin-10-yl radical (SQH2.) is described as the first air-stable, neutral phenothiazinyl free radical. The crystalline dark-blue species is characterized by means of EPR and UV/Vis/near-IR spectroscopy, as well as cyclic voltammetry, spectro-electrochemical analysis, single-crystal XRD, and computational studies. The SQH2. radical stands out from other aminyl radicals by an impressive radical stabilization energy and its parent amine has one of the weakest N−H bond dissociation energies ever determined. In addition to serving as open-shell reference in medicinal chemistry, its tridentate binding pocket or hydrogen-bond-donor ability might enable manifold uses as a redox-active ligand or proton-coupled electron-transfer reagent.
First published: 16 January 2020
Gesehen am 22.11.2021